Respuesta :
[tex]x^2-16x+64=0[/tex]
Method 1.
Use [tex](a-b)^2=a^2-2ab+b^2[/tex]
[tex]x^2-2\cdot x\cdot8+8^2=0\\\\(x-8)^2=0\\\\(x-8)(x-8)=0[/tex]
Method 2.
[tex]x^2-8x-8x+64=0\\\\x(x-8)-8(x-8)=0\\\\(x-8)(x-8)=0[/tex]
The solution to this equation is the number 8
Hey,here is the answer to ur question....
x^2-16x+64=0
Sum=-16
Product=64
So,
x^2-8x-8x+64
x(x-8) -8(x-8)
(x-8)(x-8)
=>(x-8)^2
Hope this helps u........
x^2-16x+64=0
Sum=-16
Product=64
So,
x^2-8x-8x+64
x(x-8) -8(x-8)
(x-8)(x-8)
=>(x-8)^2
Hope this helps u........